2020
DOI: 10.3390/su12031006
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Circularity—Addressing Product Design, Consumption Practices and Resource Flows in Domestic Kitchens

Abstract: Both the daily use and renewal of kitchens significantly contribute to the overall environmental impact of domestic buildings. To identify design implications related to circular consumption in domestic kitchens, 20 household interviews and one focus group session were performed, investigating how kitchens are used and transformed to meet households’ wants and needs. This study determined that daily kitchen resource use is greatly affected by kitchen design and that typical kitchen design generally does not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Some salient examples are design for upgradability ( Xing and Belusko, 2008 ), design for remanufacturing and refurbishing ( Bakker et al., 2014 ; Charter and Gray, 2008 ; Steeneck and Sarin, 2018 ; W. Wang et al., 2017 ), design for use optimization ( Mont, 2008 ), design for repairing ( Cordella et al., 2021 ; W. Wang et al., 2017 ), and design for longevity ( Carlsson et al., 2021 ). Other approaches encompass CE strategies, aiming to provide various alternatives for consideration by designers during early product development phases ( Bovea and Pérez-Belis, 2018 ), while some other approaches focus on measuring and assessing the greenness of extending the lifespan of products ( Alfieri et al., 2018 ; Desing et al., 2021 ; Franklin-Johnson et al., 2016 ; Hagejärd et al., 2020 ). CE has also been analyzed from the design process perspective, considering multiple lifecycles ( Asif et al., 2021 ), product personalization ( Maldini et al., 2019 ), and based on the morphological product structure ( Tena, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some salient examples are design for upgradability ( Xing and Belusko, 2008 ), design for remanufacturing and refurbishing ( Bakker et al., 2014 ; Charter and Gray, 2008 ; Steeneck and Sarin, 2018 ; W. Wang et al., 2017 ), design for use optimization ( Mont, 2008 ), design for repairing ( Cordella et al., 2021 ; W. Wang et al., 2017 ), and design for longevity ( Carlsson et al., 2021 ). Other approaches encompass CE strategies, aiming to provide various alternatives for consideration by designers during early product development phases ( Bovea and Pérez-Belis, 2018 ), while some other approaches focus on measuring and assessing the greenness of extending the lifespan of products ( Alfieri et al., 2018 ; Desing et al., 2021 ; Franklin-Johnson et al., 2016 ; Hagejärd et al., 2020 ). CE has also been analyzed from the design process perspective, considering multiple lifecycles ( Asif et al., 2021 ), product personalization ( Maldini et al., 2019 ), and based on the morphological product structure ( Tena, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have pointed out that kitchen alterations are driven by the lack of functional qualities of contemporary floorplans, design trends, regulations, inadequate quality of built-in materials and lack of adaptability of space that leads to unnecessary changes in surrounding layers [18]. Hagejärd et al [20] additionally found that motivations for kitchen alterations include a dissatisfaction with the kitchen typology, a lack of worksurface and storage, insufficient floor area, obsolete furniture or appliances, a wish to enhance the appearance of the kitchen, and fluctuating household sizes.…”
Section: Spatial Characteristics and Alterations Of Kitchensmentioning
confidence: 99%
“…In particular, strategies for the transition towards CE furniture models and its relation to the sustainable development goals have been the focus. Thus, the main issues addressed are the strategic organization of the furniture supply chain, with particular interest in the potential of component standardization and design strategies as a way of closing the loop in the furniture business [24,56]. Beyond this business scope, other works focus on best practices at the industrial and institutional levels [57] and on potential policy instruments and interventions through regulatory packages [54].…”
Section: Circularity In the Furniture Industrymentioning
confidence: 99%